Corporate social responsibility in the practice and in the classroom : the Middle East and North Africa region perspective - Stachowicz-Stanusch, Agata; Sergio, Rommel Pilapil; Barson, Nora; Alami, Rachid, 1954- (Research in management education and development., 2024)
"This book presenting several different cases from various parts of MENA region it showcases how companies cope with the changing economic and social challenges toward the longer-term sustainable development. Carefully selected a variety of case studies prepared by leading authors from the region offer actional insights into incorporating corporate social responsibility and sustainability practices into businesses in the MENA region. This book offers examples of how including social responsibility into everyday life can benefit organizations, society, and the environment. Further, the book provides a unique combination of academic, industrial, and local approaches. Perfect for students taking courses on strategic management, corporate social responsibility, business ethics, marketing, international bussies or sustainability business during their undergraduate degrees and at the graduate level as part of an MBA program. This book is also an indispensable resource for consulting and training companies who work with other professionals"-- Provided by publisher.